ANALISIS MOTIVASI TERHADAP KINERJA GURU DI YAYASAN SULTAN AGUNG BATAM - Yusman, Edi; Ginting, Edison (Journal of Economics, Accounting, Tax, and Management (JECATAMA), 2022)
Motivation means motion or the urge to move. The motivation of teachers within the Sultan Agung Batam Foundation is to compete in educating students and wanting to make humans useful for others. However, to become a teacher, motivation sometimes feels slack because there is pressure from school management so that they feel uncomfortable doing the work given by the school. To deal with the problem of motivation in schools, it must be taken as a serious concern in school management. The purpose of the study was to determine the motivation at the Sultan Agung Batam Foundation and to determine the performance of teachers at the Sultan Agung Batam Foundation. The method used is this research method using descriptive and verification methods. Due to the number of teachers 52 people. So this research is a population study. The results of this study are hypotheses 1 and 2 are accepted, with the conclusion that the motivation in the teacher performance process is good in the Sultan Agung Batam Foundation environment.